AIR QUALITY AFFECTED BY INDUSTRIAL ACTIVITIES GORJ COUNTY, IN THE YEAR 2010 - Roxana - Gabriela POPA; Irina-Ramona PECINGINĂ (Fiabilitate şi Durabilitate, 2011)
The paper presents the main industrial activities pollution the air, at the level of Gorj County, in the year 2010. There are mentioned gases with greenhouse effect, acid effect gases, their graphical representation and pollution produced by the main polluting agents of the county: depositing dusts and dusts in suspension.